Determinants of The Muslim Community’s Interest in Paying Professional Zakat in DKI Jakarta - Abid Abdillah (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
In this research, not all Muslim communities in DKI Jakarta can be classified as muzaki (an individual who pays zakat, a mandatory charitable contribution in Islam, to those who are eligible to receive it), as they have not met the minimum asset threshold established. However, this does not diminish the interest of the Muslim community in DKI Jakarta in paying zakat. The research involved 160 respondents from the Muslim community in DKI Jakarta, utilizing purposive sampling for data collection. The results indicate that only the digital payment variable does not significantly affect the interest of the Muslim community in paying professional zakat. In contrast, the variables of income, altruism, environment, attitude, norms, and behavior all have a significant positive impact on the interest of the Muslim community in paying professional zakat.